2023
DOI: 10.1128/spectrum.01032-23
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genetic Characterization of Conjugative Plasmids Encoding Coresistance to Ciprofloxacin and Cephalosporin in Foodborne Vibrio spp.

Abstract: Vibrio spp. used to be very susceptible to antibiotics. However, resistance to clinically important antibiotics, such as cephalosporins and fluoroquinolones, among clinically isolated Vibrio strains is increasingly common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Despite half of the CRKA strains being susceptible to ciprofloxacin, 80% of the isolates harbored the qnrS ( qnrS1 and/or S2 ) gene. The qnrS genes have been detected in a variety of microorganisms and environments, where they can be located in both the chromosome and in plasmids ( Xu et al, 2023 ). Studies have indicated an association between qnrS1 and a Tn3-like-blaTEM-1-containing transposon, leading to enhanced recombination and insertion effectiveness ( Guan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite half of the CRKA strains being susceptible to ciprofloxacin, 80% of the isolates harbored the qnrS ( qnrS1 and/or S2 ) gene. The qnrS genes have been detected in a variety of microorganisms and environments, where they can be located in both the chromosome and in plasmids ( Xu et al, 2023 ). Studies have indicated an association between qnrS1 and a Tn3-like-blaTEM-1-containing transposon, leading to enhanced recombination and insertion effectiveness ( Guan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%